“Making Sense” of Art through Design: Towards a Multisensory Theory of Reception Aesthetics - Inbal Strauss (Sillages Critiques)
According to the dominant Western paradigm of aesthetic reception, what distinguishes works of art from everyday objects is that they offer an aesthetic experience exclusively through the privileged sense of sight. Correspondingly, theories of reception aesthetics in the fine arts, which seek to understand the ways in which works of art engage viewers in the process of meaning-making, traditionally focus on visual perception. However, contemporary works of art engage so-called “viewers” in increasingly multisensory ways that warrant not only a revision of the outdated and contentious privilege of the ocular in aesthetic reception, but correspondingly, a contemporary theory of reception aesthetics that considers multisensory forms of perception. Therefore, this article asks: how might the design of everyday objects – which engage users in visual as well as tactile, proprioceptive, auditory, olfactory, and gustatory ways – contribute to a theory of reception aesthetics that can illuminate and inform the ways in which sensory works of art engage audiences in the process of meaning-making? Drawing on Wolfgang Kemp’s theory of reception aesthetics on the one hand and Donald Norman’s theory of design on the other, this article proposes a methodology for analysing the impact of artistic productions in design terms (namely, affordances, constraints, signifiers, feedback, mapping, and conceptual model). Subsequently, it offers a “keyhole” comparison of an everyday object (a Rubik’s Cube) and a multisensory work of art (Lygia Clark’s Critter [1960]), whereby the interaction analysis of the former illuminates the multisensory ways in which the latter engages its audience in the process of meaning-making.